2006
DOI: 10.1155/ijrm/2006/93621
|View full text |Cite
|
Sign up to set email alerts
|

Rotordynamics of Turbine Labyrinth Seals with Rotor Axial Shifting

Abstract: Rotors in high-performance steam turbines experience a significant axial shifting during starting and stopping processes due to thermal expansion, for example. This axial shifting could significantly alter the flow pattern and the flow-induced rotordynamic forces in labyrinth seals, which in turn, can considerably affect the rotor-seal system performance. This paper investigates the influence of the rotor axial shifting on leakage rate as well as rotordynamic forces in high-low labyrinth seals over a range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The step position and the step height were chosen to be variable. Xi [20] investigated the influence of the rotor axial shifting on the leakage rate as well as rotor-dynamic forces in high-low labyrinth seals over a range of seal clearances and inlet swirl velocities. It was also found that a less destabilizing effect arose from the rotor axial shifting in the leakage flow direction, whereas a more destabilizing effect arose from shifting against the leakage flow direction.…”
Section: Introductionmentioning
confidence: 99%
“…The step position and the step height were chosen to be variable. Xi [20] investigated the influence of the rotor axial shifting on the leakage rate as well as rotor-dynamic forces in high-low labyrinth seals over a range of seal clearances and inlet swirl velocities. It was also found that a less destabilizing effect arose from the rotor axial shifting in the leakage flow direction, whereas a more destabilizing effect arose from shifting against the leakage flow direction.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]), through more complicated two or three control volumes codes [4], to full 3D simulations using finite differences or finite volumes [5][6][7]. The later method based on the simulation of 3D turbulent flows gives the most complete description of the flow field and allows arbitrary geometric configurations of the seals but this comes at the price of an excessive amount of computational resources.…”
Section: Introductionmentioning
confidence: 99%